Kewenangan Jaksa Penuntut Umum dalam Penyelesaian Pengembalian Kerugian Keuangan Negara pada Perkara Tindak Pidana Korupsi - Helmy Febrianto Rasyd; Tofik Yanuar Chandra; Mohamad Ismed (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
The role of the Public Prosecutor in recovering state losses is not only carried out within the context of criminal law, but also through civil law mechanisms as stipulated in Article 32 of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning PTPK. Based on data from Indonesia Corruption Watch (ICW), throughout 2023 the Prosecutor's Office handled 1,649 corruption cases with a total compensation claim of IDR 82.6 trillion, contributing more than 99% of the total national compensation claim (IDR 83.3 trillion). Normatively, legal instruments have provided a framework that allows for maximum recovery of state losses. However, empirically, its implementation remains far from expectations, both in terms of the achievement of the recovery value and the effectiveness of the decision execution mechanism. This phenomenon demonstrates the gap between das sollen and das sein in law enforcement. The problem formulation raised in this study is how the process of recovering state financial losses in corruption cases and the authority of the public prosecutor in resolving the recovery of state financial losses in corruption cases. In this study, the author uses the theory of authority and the Dual Track System theory as analytical tools in dissecting this study. The research questions addressed in this study are the process of recovering state financial losses in corruption cases and the authority of public prosecutors in resolving the recovery of state financial losses in corruption cases. In this study, the author uses the theory of authority and the Dual Track System theory as analytical tools in analyzing this research. The research method used is a normative juridical legal approach. This research uses a statute approach, a case approach, a conceptual approach, and an analytical approach sourced from primary legal materials consisting of the Criminal Code, the Corruption Act and existing case studies, secondary legal materials consisting of books, research results, articles and tertiary legal materials from libraries, articles and websites. The results of this study indicate that the process of resolving the return of state financial losses in corruption crimes consists of 2 (two) mechanisms, namely through criminal and civil. Through the criminal route, it can be carried out from the investigation stage, prosecution, trial examination, to the stage of executing court decisions and the authority of the Public Prosecutor in resolving the return of state financial losses is an attribution authority that comes directly from statutory regulations, especially the Corruption Law and statutory regulations regarding the Prosecutor's Office. The suggestion in this study is that it is necessary to strengthen the strategy of tracking and securing assets from the investigation stage. In this case, the Public Prosecutor needs to optimize coordination with investigators, auditors, and related institutions in conducting comprehensive asset tracking from the initial stages of the investigation and optimizing the execution of replacement money to ensure that the replacement money crime is truly realized.